2021
DOI: 10.1007/s00415-021-10568-9
|View full text |Cite
|
Sign up to set email alerts
|

Memory enhancement by multidomain group cognitive training in patients with Parkinson’s disease and mild cognitive impairment: long-term effects of a multicenter randomized controlled trial

Abstract: Background Meta-analyses indicate positive effects of cognitive training (CT) in patients with Parkinson’s disease (PD), however, most previous studies had small sample sizes and did not evaluate long-term follow-up. Therefore, a multicenter randomized controlled, single-blinded trial (Train-ParC study) was conducted to examine CT effects in PD patients with mild cognitive impairment (PD-MCI). Immediately after CT, an enhancement of executive functions was demonstrated. Here, we present the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…With regard to CT, we previously demonstrated improvement of executive function (EF) in PD-MCI induced by multi-domain group CT, specially showing an enhanced effect for patients that were more affected [ 4 ]. Likewise, such intervention was able to improve memory function after 6 months, although the improvement was not present after 12 months, while EF remained stable in the long term [ 5 ]. Notoriously, it has recently been reported that CT increases PA in patients with PD-MCI, possibly due to effects on EF [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to CT, we previously demonstrated improvement of executive function (EF) in PD-MCI induced by multi-domain group CT, specially showing an enhanced effect for patients that were more affected [ 4 ]. Likewise, such intervention was able to improve memory function after 6 months, although the improvement was not present after 12 months, while EF remained stable in the long term [ 5 ]. Notoriously, it has recently been reported that CT increases PA in patients with PD-MCI, possibly due to effects on EF [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a multicenter (MC) study addressing the independent effect of CT and PA on cognition, we previously reported a statistical trend on the interaction between time and group (CT and PA) on overall EF and a significant effect only on phonemic fluency as a specific part of EF [ 4 ]. Moreover, we reported a significant effect on the interaction between time and group (CT and PA) on memory after 6 months of intervention, but not on EF after 6 and 12 months of intervention although EF enhancement occurred immediately after intervention [ 5 ]. Note that the MC study is slightly significant regarding the independent effect of interventions on EF, however the single center data that we consider in the present study showed no independent effect of interventions on EF, possibly due to underpower.…”
Section: Introductionmentioning
confidence: 99%
“…However, some reviews included non-randomized controlled trials (RCTs) or lacked quantitative analyses (Cusso et al, 2016;Triegaardt et al, 2020;Cartmill et al, 2021;Takamiya et al, 2021); thus, these systematic reviews did not provide strong evidence. In addition, most RCTs compared nonpharmacological interventions with placebo, waiting list, or usual treatments, and only a few RCTs compared two different non-pharmacological interventions (Modugno et al, 2010;Kalbe et al, 2020;Schmidt et al, 2021). To our knowledge, only one systematic review has reported the efficacy of nonpharmacological interventions on depression in PD subjects (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no statistically significant differences on any of the individual cognitive tests, the authors found statistically significant improvement via practice effect was more common in the placebo than treatment group. A global statistical test with unweighted z-scores or non-parametric ranks 10,11 could be useful to answer the question of impact on cognition more broadly. This would also avoid challenges associated with controlling for Type-I error and provide a meaningful metric to associate with subjective cognitive symptom reporting.…”
mentioning
confidence: 99%